Prevalence of Psychological distress among mothers of β-Thalassemia children in a developing country: Psychological distress among mothers of β-Thalassemia children - Anwar, Haniyah; Zafar, Zeeshan; Jahangir, Jawad; Khalid, Hiba; Wajid, Ayesha; Khan, Sarfraz (Pakistan Journal of Health Sciences, 2022)
Beta-thalassemia major (BTM) is one of the most common hereditary hemoglobinopathies in Pakistan, with 9.8 million persons in the general population and gene carriers (5-7%). The mothers of these chronically ill patients often endure many challenges associated with caregiving. Objective: To determine the prevalence of psychological distress experienced by mothers of children suffering from BTM in a developing country. Methods: From March 2022 to August 2022, this descriptive cross-sectional study was done among mothers of thalassemic children who presented to the Outpatient Department of Benazir Bhutto Hospital in Rawalpindi. A self-structured questionnaire consisting of 1) Socio-demographic characteristics and 2) the Kessler-10 (K-10) Distress Measure was used to collect data. To determine the level of psychological distress among mothers of children, a descriptive analysis was done. The Spearman correlation was used to explore the relationship between demographic factors and the level of psychological distress experienced by mothers of children with thalassemia. Results: The mean age of mothers being interviewed was 37.65±3.63 years. Out of 83 mothers, 54 (65.1%) had psychological distress. The children's age (r= -.275) and any psychological support taken by mother (r= -.253) were correlated (p < .05) negatively with the severity of psychological distress. Conclusions: Our study identified that most mothers of children suffering from thalassemia had psychological distress. Thus, these mothers are at risk of poor health outcomes and should be targeted for screening and treatments focused on improving their health and well-being